The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.12691/jfnr-2-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Nutritional Properties and Antioxidant Activity of Monkey Apple (<i>Anisophyllea laurina </i><i>R</i><i>.</i><i> </i><i>Br. ex Sabine</i>)

Abstract: The aim of this study was to determine the chemical composition, nutritional properties and antioxidant activity of Monkey apple methanol extract. Results expressed on dry matter basis revealed the seeds contained the following: 2.74% protein, 15.86% crude fat, 7.67% crude fiber, 468.74kcal, 82.01% moisture content, 5.72% ash, 88.98% carbohydrate. The seeds further contained considerable amounts of minerals and vitamins as follows: 14.14mg/100g for iron, 2.37mg/100g for potassium, 1434.38mg/100g for manganese,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…40 Proper food processing would reduce these anti-nutrients. The phytate content of avocado seed is lower than that of locust bean pulp as reported (6.28±0.06 mg/100 g) by Dahouenon-Ahoussi et al 41 Adegoke et al 42 reported higher values for tannin, oxalate and phytic acid (11.29 g/100 g, 4.07 g/100 g and 12.87/100 g) respectively for avocado seed; however, boiling for 25 min and soaking for 24 hrs effectively reduced the anti-nutritional factors without any adverse effect on the nutritional quality. The anti nutritional components of Terminalia catappa (almond) seeds shows higher values when compared with those of avocado seed.…”
Section: Resultsmentioning
confidence: 58%
“…40 Proper food processing would reduce these anti-nutrients. The phytate content of avocado seed is lower than that of locust bean pulp as reported (6.28±0.06 mg/100 g) by Dahouenon-Ahoussi et al 41 Adegoke et al 42 reported higher values for tannin, oxalate and phytic acid (11.29 g/100 g, 4.07 g/100 g and 12.87/100 g) respectively for avocado seed; however, boiling for 25 min and soaking for 24 hrs effectively reduced the anti-nutritional factors without any adverse effect on the nutritional quality. The anti nutritional components of Terminalia catappa (almond) seeds shows higher values when compared with those of avocado seed.…”
Section: Resultsmentioning
confidence: 58%
“…Other authors perform a qualitative analysis of apple juices [10,11]. Regarding the chemical composition of apples and their juices, the topic is well developed, for example, such data give [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26] and others.…”
Section: Technological Parametersmentioning
confidence: 99%
“…Total fat of alternative milk were determined according to James (1995). Total carbohydrate content (on dry weight basis) was calculated by difference according to Onivogui et al (2014). Energy value of alternative milk was estimated according to the method described by Hunt et al (1987).…”
Section: Chemical Analysismentioning
confidence: 99%